2020
DOI: 10.3390/cancers12020516
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein 4 Targeting Glioma Stem-Like Cells for Malignant Glioma Treatment: Latest Advances and Implications for Clinical Application

Abstract: Malignant gliomas are heterogeneous neoplasms. Glioma stem-like cells (GSCs) are undifferentiated and self-renewing cells that develop and maintain these tumors. These cells are the main population that resist current therapies. Genomic and epigenomic analyses has identified various molecular subtypes. Bone morphogenetic protein 4 (BMP4) reduces the number of GSCs through differentiation and induction of apoptosis, thus increasing therapeutic sensitivity. However, the short half-life of BMP4 impedes its clinic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 80 publications
0
11
0
2
Order By: Relevance
“…BMP4 is strongly associated with GBM stem cell differentiation [ 29 , 30 , 31 ], and has been reported as a potential anti-GBM target [ 32 ]. Since BIRC3 expression is associated with GBM cell self-renewal and stemness maintenance, we wanted to determine if there was any correlation between BIRC3 expression and BMP4 signaling activation.…”
Section: Resultsmentioning
confidence: 99%
“…BMP4 is strongly associated with GBM stem cell differentiation [ 29 , 30 , 31 ], and has been reported as a potential anti-GBM target [ 32 ]. Since BIRC3 expression is associated with GBM cell self-renewal and stemness maintenance, we wanted to determine if there was any correlation between BIRC3 expression and BMP4 signaling activation.…”
Section: Resultsmentioning
confidence: 99%
“…BMPs suppress the tumorigenic function of human glioma-initiating cells by inducing cell differentiation, cell cycle arrest, and apoptosis (see below). Accordingly, several reports have shown that BMP-4 is expressed in low-grade gliomas, and that it serves as a favorable prognostic marker in gliomas ( Bao et al, 2013 ; Nayak et al, 2020 ). BMP-4 is overexpressed in gliomas harboring IDH1 mutations, which are a hallmark of better prognosis ( Zhou et al, 2020 ).…”
Section: Altered Expression Of Bone Morphogenetic Proteins and Their ...mentioning
confidence: 99%
“…Bone morphogenic protein 4 (BMP4) has previously been shown to effectively reduce the GSC pool in GBM [ 30 ]. As a proof of principle, we treated highly clonogenic JHH520 and 407 cells with 50 ng/mL BMP4 for 48 h and observed significantly increased expression of the differentiation marker glial fibrillary acidic protein ( GFAP ) and reduced expression of two stemness markers ( CD133 and SOX2 ).…”
Section: Resultsmentioning
confidence: 99%